Risk Factors Associated with Colorectal Cancer at Abdoel Moeloek Regional General Hospital, Lampung Province - Syazili Mustofa; Andika Ridwan Nugraha Harahap (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Colorectal cancer is a malignant neoplasm originating or growing in the colon and rectum, which become one of the malignant diseases with the highest prevalence in Indonesia. This research aimed to determine the association between risk factors and the incidence of colorectal cancer in RSUD Dr. H. Abdul Moeloek Bandar Lampung. This research was conducted from May to July 2018 at RSUD Dr. H. Abdul Moeloek Bandar Lampung, using the observational analytic method and a case-control design. The sample of this research consisted of 92 respondents, which was determined using the consecutive sampling technique—a measurement method used in the form of interviews and medical records. Data was processed using a statistical test with a 0.05 confidence level. The result of the Chi-square test showed that there was an association between age (p = 0.01), physical activity (p = 0.001), smoking history (p = 0.001), alcohol consumption history (p = 0.021), and diabetes Mellitus history (p = 0.012) with the incidence of colorectal cancer. There was an association between age, physical activity, smoking history, alcohol consumption history, and diabetes Mellitus history with the incidence of colorectal cancer in RSUD Dr. H. Abdul Moeloek Bandar Lampung.